An intervention based on video feedback and questioning to improve tactical knowledge in expert female volleyball players - Moreno, M. P.; Moreno, A.; Garcia-Gonzalez, L.; Ureña, A.; Hernández, C.; Del Villar, F. (Perceptual and Motor Skills, 2016)
The objective of the study was to develop and apply a tactical-cognitive training program based on the use of video feedback and questioning in real game time, in order to improve tactical knowledge in volleyball. A two-group quasi-experimental design was used with a sample of eight female players (M = 14.8 yr., SD = 0.7), who were divided into an Experimental group (n = 4) and a Control group (n = 4). The independent variable was the tactical-cognitive training program, which was applied for 11 wk. in a 6 × 6 game situation training context. The dependent variable was tactical knowledge, which was measured by problem representation and strategy planning with a verbal protocol. The results showed that after applying the intervention program the players in the Experimental group showed more complex, sophisticated, and structured tactical knowledge, compared with the players from the Control group. These results suggest that complementing the training process with cognitive tools may enable athletes to increases their tactical behavior and presumably improve their performance.